The potential immuno-stimulating effect of curcumin, piperine, and taurine combination in hepatocellular carcinoma; a pilot study - Raghda R. kotb; Ahmed M. Afifi; Motawa E. EL-Houseini; Mohamed Ezz-Elarab; Emad B. Basalious; Mervat M. Omran; Mona S. Abdellateif (Discover Oncology, 2023)
Abstract Background This is a phase II clinical trial to investigate the immunotherapeutic effect of Curcumin, Piperine, and Taurine (CPT) combination in hepatocellular carcinoma (HCC). Methods Twenty-six HCC patients aged (50–80 years) were recruited for administration of a daily dose of 5 g of curcumin, 50 mg of piperine, and 500 mg of taurine divided into three doses for successive 3 months. The three components (CPT) were prepared in one capsule. Patients were assessed after each month (cycle) for the plasma levels of CD4, CD8, CD25, Interleukins-2 (IL-2), IL-6, IL-12, Interferon-gamma (IFN- γ), Lactate dehydrogenase (LDH), and Vascular endothelial growth factor (VEGF), FOXP3 mRNA, and miRNA 21. Results There was a significant increase in the plasma levels of CD4 and CD8, while a significant decrease in the CD25 level after the second and third cycles compared to the baseline level [P < 0.001 for both]. Also, there was a significant increase in the plasma levels of IL-2, IL-12, and IFN-γ [ P = 0.001, P = 0.006, and P = 0.029; respectively], while there was a significant decrease in IL-6, VEGF-α, LDH, and Alpha-fetoprotein (AFP) after CPT administration compared to the baseline levels [P < 0.001, P < 0.001, P = 0.020, and P = 0.004; respectively]. The expression level of miRNA-21 was significantly decreased after CPT administration compared to the baseline level [5.5±0.88, 4.1±0.78, 3±0.75, and 2.5±0.76; respectively, P<0.001]. Though there was a noticeable decrease in the FOXP3 expression after each cycle, however, it didn’t reach a significant level [5.3±0.8, 4.2±0.76, 3.2±0.67, and 2.5±0.79; respectively, P=0.184]. Conclusion CPT could exhibit a potential immune-stimulating effect in HCC patients. The current trial had been registered at the National Hepatology and Tropical Medicine Research Institute (NHTMRI), with a registration number of NHTMRI-IRB 2-21 on 5th January 2021.